GURU, LINGKUNGAN, DAN KEBIASAAN BELAJAR: KUNCI EFISIENSI PEMBELAJARAN DI SEKOLAH DASAR - Ayu Dwi Yanti; Sumardi W Ndolu (Universitas Nusa Cendana, 2026)
Learning efficiency in elementary schools depends on three main domains, namely teacher competence, the quality of the learning environment, and students’ learning habits. Teachers hold a strategic role as activity designers, facilitators of interaction, and drivers of learning motivation. Meanwhile, the learning environment both physical and social, including the family serves as an important determinant of students’ comfort and readiness in participating in the learning process. Learning habits, which include time management, the use of appropriate learning strategies, and self-reflection skills, also contribute significantly to learning success. This article is a literature study that examines the relationship among these three factors through an analysis of various scientific sources and relevant research findings within the context of elementary education. The results of the review indicate that the integration of effective teaching practices, supportive learning environments, and systematic learning habits contributes to improving learning efficiency without reducing the depth of understanding. These findings emphasize the need for collaboration among teachers, families, and schools to create a learning ecosystem that can optimally support students’ achievement of basic competencies.